2018
DOI: 10.1152/advan.00064.2018
|View full text |Cite
|
Sign up to set email alerts
|

Best practices in active and student-centered learning in physiology classes

Abstract: This review article includes our analysis of the literature and our own experiences in using various types of active learning as best practices for evidence-based teaching in physiology. We have evaluated what physiology students should be expected to learn and what are specific challenges to enhancing their learning of physiology principles. We also consider how the instructor should design his or her teaching to improve buy-in from both students and other faculty members. We include a discussion of how the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 55 publications
8
79
1
8
Order By: Relevance
“…Student-centered learning (also known as learner-centered pedagogy) is based on constructivist learning theory and supports student learning by allowing students to make decisions in their learning (Goodman et al 2018;Hannafin and Land 1997;Wright 2011). Dockterman's (2018) overview of the history of personalized learning informs us that students learn more effectively when instruction is individualized to the learners' needs and that a new pedagogy of personalization recognizes that each student is different.…”
Section: Pedagogies Of Adaptive Learningmentioning
confidence: 99%
“…Student-centered learning (also known as learner-centered pedagogy) is based on constructivist learning theory and supports student learning by allowing students to make decisions in their learning (Goodman et al 2018;Hannafin and Land 1997;Wright 2011). Dockterman's (2018) overview of the history of personalized learning informs us that students learn more effectively when instruction is individualized to the learners' needs and that a new pedagogy of personalization recognizes that each student is different.…”
Section: Pedagogies Of Adaptive Learningmentioning
confidence: 99%
“…Taking together, our results are important for physiology education. Previous research demonstrated that physiology is hard to learn, and professors expect more than just learning from their students ( 8 , 10 ). Goodman and others ( 8 , 9 , 11 ) notice that the amount of content in physiology classes is one of the most challenging obstacles to the students’ learning.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research demonstrated that physiology is hard to learn, and professors expect more than just learning from their students ( 8 , 10 ). Goodman and others ( 8 , 9 , 11 ) notice that the amount of content in physiology classes is one of the most challenging obstacles to the students’ learning. In this regard, providing opportunities to promote contact with physiology content after concluding the physiology course contributes to a better understanding of some content that may not have been completely understood during the course, to elucidate misconceptions, to update information according to recent discoveries, and to review information previously learned so that it will not be forgotten ( 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the last decades, a university classroom has evolved into an active learning and a more student-centered environment in which the student learns through proactive work rather than as a passive receptor (7,17). Several advantages of active learning have been observed, such as promoting a more inclusive classroom, improving students' argumentation, and enhanced student satisfaction and motivation, among others (7,9,14). Therefore, making lectures as interactive as possible and creating environments that facilitate learning are important objectives for the medicine and physiology teacher (9,22).…”
Section: Introductionmentioning
confidence: 99%
“…Several advantages of active learning have been observed, such as promoting a more inclusive classroom, improving students' argumentation, and enhanced student satisfaction and motivation, among others (7,9,14). Therefore, making lectures as interactive as possible and creating environments that facilitate learning are important objectives for the medicine and physiology teacher (9,22).…”
Section: Introductionmentioning
confidence: 99%